Graduated Compression Stockings as an Adjunct to Low Dose Low Molecular Weight Heparin in Venous Thromboembolism Prevention in Surgery: A Multicentre Randomised Controlled Trial. (June 2017) - Shalhoub, J.; Norrie, J.; Baker, C.; Bradbury, A.W.; Dhillon, K.; Everington, T.; Gohel, M.S.; Hamady, Z.; Heatley, F.; Hudson, J.; Hunt, B.J.; Lawton, R.; et al.
Abstract : Background: The evidence base upon which current global venous thromboembolism (VTE) prevention recommendations have been made is not optimal. The cost of purchasing and applying graduated compression stockings (GCS) in surgical patients is considerable and has been estimated at £63.1 million per year in England alone. Objective: The aim was to determine whether low dose low molecular weight heparin (LMWH) alone is non-inferior to a combination of GCS and low dose LMWH for the prevention of VTE. Methods: The randomised controlled Graduated compression as an Adjunct to Pharmacoprophylaxis in Surgery (GAPS) Trial (ISRCTN 13911492) will randomise adult elective surgical patients identified as being at moderate and high risk of VTE to receive either the current "standard" combined thromboprophylactic LMWH with GCS mechanical thromboprophylaxis, or thromboprophylactic LMWH pharmacoprophylaxis alone. To show non-inferiority (3.5% non-inferiority margin) for the primary endpoint of all VTE within 90 days, 2236 patients are required. Recruitment will be from seven UK centres. Secondary outcomes include quality of life, compliance with stockings and LMWH, overall mortality, and GCS or LMWH related complications (including bleeding). Recruitment commenced in April 2016 with the seven UK centres coming "on-line" in a staggered fashion. Recruitment will be over a total of 18 months. The GAPS trial is funded by the National Institute for Health Research Health Technology Assessment in the UK (14/140/61).